2009
DOI: 10.1007/s12010-009-8849-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pro-inflammatory Secreted Phospholipase A2 by Extracts from Cynara cardunculus L.

Abstract: The aim of the present work was to evaluate the anti-inflammatory properties of Cynara cardunculus L. (Asteraceae) during its growth using various solvents such as n-hexane, dichloromethane, acetone, and methanol for air-dried leaves and stems. The anti-inflammatory activities of crude extracts were evaluated by measuring the inhibition potency of mammalian non-pancreatic phospholipases A2 (hG-IIA). The methanol and acetone extracts of leaves harvested in February exhibit potent inhibition of hG-IIA (IC(50) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…More interestingly, the highest phenolics and flavonoids concentration recorded under high chloride concentration ( Table 3 ) are also important to human health, and therefore they attribute an added value (compared to the control) to the nutraceutical properties of cardoon leaf extract. These results are very important because several pharmacological studies have demonstrated that cardoon extracts are supposed to exert antimicrobial, anti-inflammatory, anti-oxidative, anti-carcinogenic, bile-expelling and urinative activities, as well as the ability to inhibit low-density lipoprotein (LDL) oxidation and cholesterol biosynthesis ( Falleh et al, 2008 ; Kukíc et al, 2008 ; Kammoun et al, 2010 ; Mileo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the highest phenolics and flavonoids concentration recorded under high chloride concentration ( Table 3 ) are also important to human health, and therefore they attribute an added value (compared to the control) to the nutraceutical properties of cardoon leaf extract. These results are very important because several pharmacological studies have demonstrated that cardoon extracts are supposed to exert antimicrobial, anti-inflammatory, anti-oxidative, anti-carcinogenic, bile-expelling and urinative activities, as well as the ability to inhibit low-density lipoprotein (LDL) oxidation and cholesterol biosynthesis ( Falleh et al, 2008 ; Kukíc et al, 2008 ; Kammoun et al, 2010 ; Mileo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches for evaluating the significance of phospholipases as virulence factor for the disease and identification of its inhibitors from different anti-fungal or antibacterial herbs or by chemical inhibitor would be potentially an effective therapy for several inflammatory conditions. PLA 2 inhibitors are used as potential anti-inflammatory agents for inhibition of PLA 2 activity and are suggested for their therapeutic use [193,194]. The starting point in seeking new and specific anti-inflammatory drug against such enzymes (PLs) are ellagic acid derivatives, koninginins E and F. Ellagic acid derivatives isolated from Casearia sylvestris.…”
Section: Discussionmentioning
confidence: 99%
“…Some partial in vitro and in vivo studies (Kammoun et al, ; Mohamed et al, ; Chagas‐Paula et al, ) show the effective antiinflammatory properties of artichoke ( Cynara cardunculus L.; Asteraceae family) extracts, but the effect of artichoke on the activity of AKR1B1 had not been studied prior to the work we are reporting here.…”
Section: Introductionmentioning
confidence: 97%